Evaluating the fracture toughness of layered pressure vessel steels. (15th February 2019) - Joyce, James A.; Wells, Doug; Stoltz, Brian; Shelton, Levi; Jacobs, Preston; Link, Richard E.
Highlights: Assure structural integrity of NASA layered pressure vessels. Apply ASTM E1820 and E1921 to toughness evaluations of legacy pressure vessel steels. Apply E1921 inhomogeneity analysis to welds and weld heat affected zones. Combine toughness properties from multiple vessels using E1921 inhomogeneity analysis. Abstract: This paper describes testing conducted on dis-assembled layered pressure vessels to determine the fracture toughness properties of the component structural steels used in their construction. These vessels are part of a large number of similar vessels used at NASA laboratory facilities which were constructed during the 1950s and 1960s to support the then expanding space program. Fracture toughness properties are determined for the ferritic structural steels according to the ASTM standards E1820 and E1921 and the intention is to use the properties obtained from a small number of sacrificed vessels to assure the safety of the remaining vessels. This paper describes the NASA program briefly and the preliminary data obtained more extensively. The steels used to construct the vessels are no longer used in pressure vessel construction but are present in many structures that exist throughout the world that date from the same time period. The properties are hence important and useful beyond the more narrow NASA application. A discussion is also included on the applicability of the modern ASTM fracture toughness tests to evaluate the fracture toughness properties of these early high strength pressure vessel steels.